2015
DOI: 10.1038/ejhg.2015.222
|View full text |Cite|
|
Sign up to set email alerts
|

Genome-wide association studies identify genetic loci for low von Willebrand factor levels

Abstract: Low von Willebrand factor (VWF) levels are associated with bleeding symptoms and are a diagnostic criterion for von Willebrand disease, the most common inherited bleeding disorder. To date, it is unclear which genetic loci are associated with reduced VWF levels. Therefore, we conducted a meta-analysis of genome-wide association studies to identify genetic loci associated with low VWF levels. For this meta-analysis, we included 31 149 participants of European ancestry from 11 community-based studies. From all p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
53
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(56 citation statements)
references
References 47 publications
2
53
0
Order By: Relevance
“…An increased median patient age, differences in ethnicity, inclusion/ exclusion criteria related to VWF:Ag levels, and a lower proportion of VWF mutation-negative patients in the Dutch population may explain these differences. Consistent with our results, however, a GWAS found that the STAB2 SNV rs4981022 associates with low VWF plasma levels (24). Further studies on the influence of rare and common STAB2 variants on the type 1 VWD phenotype are required to better understand this relationship.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…An increased median patient age, differences in ethnicity, inclusion/ exclusion criteria related to VWF:Ag levels, and a lower proportion of VWF mutation-negative patients in the Dutch population may explain these differences. Consistent with our results, however, a GWAS found that the STAB2 SNV rs4981022 associates with low VWF plasma levels (24). Further studies on the influence of rare and common STAB2 variants on the type 1 VWD phenotype are required to better understand this relationship.…”
Section: Discussionsupporting
confidence: 80%
“…While the exact mechanistic basis by which this variant modifies stabilin-2 expression is not yet known, in silico CentroidFold (http://rtools.cbrc.jp/centroidfold/) analysis predicts LSECs have the highest endocytic capacity of any cell in the body, and are reported to express a series of endocytic receptors including stabilin-2, CLEC4M, the mannose receptor, SR-A1, SR-B1, CD36, stabilin-1, FcγRIIb2, LSECtin, LRP-1, and LYVE-1. Both stabilin-2 and CLEC4M have been identified by GWAS as associating with plasma VWF or FVIII levels in normal individuals (18,24,25). In these studies, we characterize the scavenger receptor stabilin-2 as a novel clearance and immunomodulatory receptor for the human VWF-FVIII complex.…”
Section: Discussionmentioning
confidence: 94%
“…26 These loci may contain novel genes whose products regulate endothelial or platelet exocytosis. 7 For example, the CHARGE Consortium identified over 50 single nucleotide polymorphisms (SNPs) linked to altered VWF levels that are located within or near the gene encoding syntaxin-binding protein 5 ( STXBP5 ).…”
Section: Introductionmentioning
confidence: 99%
“…In the next decade, our understanding of inherited bleeding disorders and the appropriate use of pro-coagulant therapy will evolve as high throughput gene sequencing tests are being developed to assess bleeding disorders in a highly specific manner [27]. Indeed there are new genomic loci for VWD being determined and our understanding of the downstream disruption of the coagulation pathway from having a low VWF: RCo levels will become better characterized and even potentially personalized [28].…”
Section: Discussionmentioning
confidence: 99%